PENGARUH MODEL GAME BASED LEARNING TERHADAP KEMAMPUAN BERHITUNG PENJUMLAHAN DAN PENGURANGAN BILANGAN CACAH SISWA KELAS 1 SDN WONOPLEMBON 01 - Saputro, Ilham cahyo; Sari, Elok Fariha Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the Game Based Learning (GBL) model on the arithmetic skills of first grade students at SDN Wonoplembon 01, particularty in addition and subtraction of whole numbers. The background of this research lies in the low motivation and arithmetic skilss of students due to the use of conventional teaching methods. This study employs a quantitative approach with a quasi experimental design using the noneequivalent control group design model. The sample consisted of two classes an experimental class that received Game Based Learning (GBL) instruction and a control class with conventional methods. Data were collected through pretest and posttest to evaluate changes in students arithmetic performance. The results revealed a significant improvement in the experimental groups arithmetic ability compared to the control group. The application of Game Based Learning (GBL) facilitated a more engaging,interactive,and enjoyable learning environment, which contributed to better conceptual understanding and higher students motivation. Therefore, this study concludes that the Game Based Learning model positively affects students arithmetic abilities in early grade mathematics learning.